As formas geométricas no espaço escolar - Lourdes , Dayane Freitas de; Gomes, Daura Janes; Macedo, Katiana de Oliveira; Bassan, Osvalda; Franco , Elaine; Brito , Nemaflavia Gomes Feitoza; Carvalho , Elisângela Oliveira; Ferreira , Luciana Lopes; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf